Basic essential education program (BEEP): a brief introductory faculty development course for medical teachers - Madan, Robert; Hawa, Raed; Ballon, Bruce; Silver, Ivan; Bernstein, Stacey (Canadian Medical Education Journal, 2012)
Background: Physicians have a unique role in teaching future physicians and allied health professionals. Yet, most medical doctors have limited instruction in this critical component of their daily activity. Methods: This study was a prospective cohort study of the effectiveness of a local teaching program at two teaching hospitals for junior faculty. Based on a needs analysis and literature review, the teaching program was developed in an accessible and compact format of six consecutive, one-hour "lunch and learn" sessions, held locally over a six week period. Pre-post questionnaires and focus groups were used to evaluate the program. Results: Participants reported being satisfied with the course as whole, particularly in respect to the format and location. There was an improvement in their knowledge in all content areas covered. The greatest benefits were derived from fostering a community of practice and having the opportunity to role play and simulate teaching skills. An attitudinal change towards teaching was noted. Conclusions: A brief, local faculty development program was effective in enhancing physicians’ knowledge, skills, and attitudes in teaching.